Asymmetric DSL Technology of Signal Transmission - Kovačević, Dražen; Haramina, Hrvoje; Greiner, Ervin (Promet - Traffic&Transportation, 2005)
Asymmetric flow of information is the key feature of theADSL (Asymmetric Digital Subscriber Loop) technology, i.e.higher data transmission rate towards the user than from theuser towards the network. Characteristic is the short messagesending by the user with a certain request to the se!Ver. These!Ver responds to the request by a significantly longer messageof various electronic forms (data, digitized speech, pictures orvideo). Therefore, this technology is most often used by smalland medium users. ADSL is currently the only commerciallyavailable DSL technology which is still experiencing the breakthroughon the seiVice market. It enables faster access to theInternet, LAN (Local Area Network), videoconferencing, VoD(Video on Demand) and interactive multimedia. In order tostandardize such se/Vices, the !TU (International TelecommunicationsUnion) G. 992.1 (standardized DMT-discrete multi-tone line coding technology) and ANSJ (American NationalStandards Institution) Tl.413-95!98 are used for ADSL. DMT(Discrete Multi Tone), as the more popular one, uses the linecoding technique, which splits a certain frequency range intoseveral sub-channels. Most of these sub-channels are used forupstream and downstream transmission of speech and data,whereas some are used as pilot signals or kept in rese/Ve. Suchmodulation technique expands the frequency spectrum, allowingthe usage ofbroadband se/Vices per one pair of wires. In thisway the sharing of speech and data se/Vice transmission is realized.